An augmented reality location detection system for education - Imee Shahnaz, Binti Mohd Bashah (University Malaysia Sarawak, UNIMAS., 2005)
The main focus of the project is to develop an augmented reality system as a teaching aid for student. Augmented reality can be defines as a system that permits user to view the virtual images that superimposed with the real world. The development of the system is based on the prototype given and been modified based on the chosen topic. System will detect the location of the object and display the virtual alphabet. Then, it will pronounce the chosen object. Method that been use in developing the system is image processing, location detection and voice application. The proposition in developing the system is to assist student in their early learning process. It can also help and boost students' learning ability especially children, to understand more about the world around them. The development of system is not limited for education only, but can be applied in other fields such as medical, engineering, design, tourism and other related studies.